2022
DOI: 10.3390/ijerph19020921
|View full text |Cite
|
Sign up to set email alerts
|

Employee Voice: A Mechanism to Harness Employees’ Potential for Sustainable Success

Abstract: Listening to employees’ concerns reduces their dissatisfaction, but moreover, for an organization to achieve sustainable success, employees must raise their creative voice and give their input in decision-making without the fear of rejection in a psychologically safe environment. Ethical leaders facilitate such a participative style of management. A bureaucratic culture, as is generally encountered in Pakistan’s work settings, poses real challenges to those who dare to speak up, therefore the importance of eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 94 publications
(123 reference statements)
2
9
0
Order By: Relevance
“…After filtering and deleting invalid questionnaires that were not completely filled out or selected the same options for all items or otherwise obviously not answered carefully, a total of 459 valid research results were finally obtained from 89 work teams, with a valid recovery rate of 91.80%. The response rate (i.e., >70%) further reduced the nonresponse bias [ 65 ]. Despite the non-response bias, it was felt that the sample provides the mixture of employees from various departments and the number of responses is reasonable to undertake meaningful analysis [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…After filtering and deleting invalid questionnaires that were not completely filled out or selected the same options for all items or otherwise obviously not answered carefully, a total of 459 valid research results were finally obtained from 89 work teams, with a valid recovery rate of 91.80%. The response rate (i.e., >70%) further reduced the nonresponse bias [ 65 ]. Despite the non-response bias, it was felt that the sample provides the mixture of employees from various departments and the number of responses is reasonable to undertake meaningful analysis [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because prohibitive voice is involved in expressing opinions on negative aspects in the workplace, internal auditors may perceive that prohibitive voice "carries far more personal risk" compared with promotive voice. Similarly, previous studies have found that prohibitive voice has a stronger relationship with psychological safety than does promotive voice (Röllmann et al, 2021;Zhu et al, 2022). Given prior studies (Kirk-Brown and Van Dijk, 2016) have found that the perception of psychological safety was positively related to organizational commitment, it seems sensible that internal auditors with greater derived social commitment would take a risk to raise up problematic sustainability issues.…”
Section: Limitations and Future Researchmentioning
confidence: 88%
“…Although each of the aforementioned study variable is not a new-born concept, existing literature comprehend them as critical variable help to sustain organizational success. For instance, employee voice is understood as the sharing of opinions, concerns, and suggestions to improve or recover the current situation going on at the organization [ 1 , [7] , [8] , [9] , [10] ]. Likewise, some studies discussed EVB as a critical factor for organizational behaviour sustainability [ 1 , [8] , [9] , [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, employee voice is understood as the sharing of opinions, concerns, and suggestions to improve or recover the current situation going on at the organization [ 1 , [7] , [8] , [9] , [10] ]. Likewise, some studies discussed EVB as a critical factor for organizational behaviour sustainability [ 1 , [8] , [9] , [10] , [11] , [12] , [13] ]. Also, the term organizational justice is viewed as employee perceptions of what is fair and what is unfair in their workplaces [ 2 , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%